Impact of Tibetan plateau warming amplification on the interannual variations in East Asia Summer precipitation - XiaoJing Jia; XinHai Chen; Wei Dong; Hao Ma; JingWen Ge; QiFeng Qian (npj Climate and Atmospheric Science)
Abstract The amplified warming on the Tibetan Plateau (TA) is a distinctive characteristic of global climate change, leading to various climate responses with far-reaching implications. This study investigates the influence of interannual variation of TA on summer precipitation over East Asia (Pre_EA) using observational data and a Linear Baroclinic Model (LBM). When TA exceeds the Northern Hemisphere average, summer precipitation in the Yangtze River Valley significantly decreases, while it increases in North China and South China, resulting in a tripole Pre_EA pattern. Notably, the relationship between TA and Pre_EA is independent of the El Niño-Southern Oscillation (ENSO) and explains more variance in Pre_EA than ENSO. Our analysis reveals that TA enhances the tripole Pre_EA pattern by modulating moisture transport and vertical motion in the East Asia-North Pacific regions. Specifically, positive TA is linked to significant local tropospheric warming, which intensifies and eastward expands the South Asian High, creating a double-gyre meridional circulation over East Asia. Additionally, positive TA induces an eastward-propagating wave, reinforcing a midlatitude anomalous high-pressure belt over East Asia and the western North Pacific regions. These circulation changes weaken the East Asian subtropical jet, form a notable double jet configuration, and promote subsidence over mid-latitude East Asia. Moreover, anomalously warm sea surface temperatures in the Northwestern Pacific reinforce the TA-Pre_EA relationship by contributing to the mid-latitude East Asia-North Pacific high-pressure belt. Our LBM model experiments support these findings. Our study provides an in-depth understanding of the physical processes influencing summer precipitation variability in East Asia.